2017
DOI: 10.1016/j.ijid.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of the SAPS II and SOFA scoring systems in Hanta virus Hemorrhagic Fever with Renal Syndrome

Abstract: Background: Hemorrhagic Fever with Renal Syndrome (HFRS), caused by the hantavirus, is a natural infectious disease characterized by fever, hemorrhage and renal damage. China is the most severely endemic area for HFRS in the world. In recent years, critical scoring systems based on quantitative classification have become an important clinical tool for predicting and evaluating the prognosis of critical illness, and provide guidelines for clinical practice. Methods: The sample comprised 384 patients with HFRS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…It was reported that elevated levels of CRP and PCT were present in more than 90% of patients with HFRS [9]. The elevated level of PCT in HFRS may be related with and immune activation caused by hantavirus [10]. As well as elevated C-reactive protein levels were shown to in patients with hantavirus infection.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It was reported that elevated levels of CRP and PCT were present in more than 90% of patients with HFRS [9]. The elevated level of PCT in HFRS may be related with and immune activation caused by hantavirus [10]. As well as elevated C-reactive protein levels were shown to in patients with hantavirus infection.…”
Section: Discussionmentioning
confidence: 95%
“…As well as elevated C-reactive protein levels were shown to in patients with hantavirus infection. But whether the elevation of CRP and PCT were associated with the severity of HFRS is still a controversial issue [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the coagulation system [ 26 , 27 ], severe infection [ 13 15 , 21 , 25 ], inflammatory diseases [ 18 ], trauma [ 28 ], cardiovascular diseases [ 19 ], and thrombotic diseases [ 29 ] could all result in changes in platelet parameters. Previous study showed that PLT counts were negatively correlated with the progression of HFRS, and the AUC values were 0.814 for the severity of HFRS, which indicated the better predictive efficacy of PLT counts [ 11 ]. However, the patients in that study [ 11 ] were just divided into mild group and severe group, and no analysis of the predictive value of platelet parameters was conducted in HFRS patients in relation to the patients' survival.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that PLT counts were negatively correlated with the progression of HFRS, and the AUC values were 0.814 for the severity of HFRS, which indicated the better predictive efficacy of PLT counts [ 11 ]. However, the patients in that study [ 11 ] were just divided into mild group and severe group, and no analysis of the predictive value of platelet parameters was conducted in HFRS patients in relation to the patients' survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation